Comparative evaluation of packed-bed performance of biomass ashes as adsorbents for removal of diuron from aqueous solution. Issue 59 (19th December 2016) - Deokar, Sunil K.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D.
Abstract: The packed-bed performance of biomass ashes (BMA), namely rice husk ash (RHA) and bagasse fly ash (BFA), was investigated for adsorptive removal of diuron (herbicide) under dynamic conditions. The effects of influent concentration (10–30 mg/L), flow rate (1–3 mL/min), and bed height (3–11 cm) were studied at 30°C and results were analyzed using various packed-bed models. The saturation time and capacity of the BFA bed were found to be approximately 1.5 and 1.6 times higher due to higher BET surface area than that of RHA bed. However, the bed utilization of RHA was higher because of smaller mass transfer zone. At a constant influent concentration (20 mg/L) and flow rate (1 mL/min), the maximum volume of diuron treated was 1, 325 and 1, 685 mL using RHA (bed height 10 cm) and BFA (bed height 11 cm), respectively. Among the packed-bed models applied, the BDST model revealed the inconsistent MTZ and complex mechanism involving more than one rate-controlling step for the adsorption of diuron on both ashes. The kinetics in the initial part of the breakthrough curve was governed by external mass transfer according to the Bohart–Adams and Wolborska models. Better agreements between experimental and predicted values of bed capacities for each ash and the higher bed capacity of BFA than RHA were demonstrated by the Thomas model. The Yoon–Nelson model was found to be superior for BFA rather than for RHA to estimate 50% saturation time. However, the deactivation kinetic model, previously discovered and applied only for gas–solid adsorption, was found to be the best for the diuron–BMA (liquid–solid) adsorption system in this study.